Dionysian and Apollonian in Advertising The Representations of Pleasure and Discipline in Finnish Television Advertisements - Sarpavaara, Harri (Qualitative Sociology Review, 2007)
The recent accounts of our era usually argue that pleasure, sensuality, and sexuality play essential roles in media and consumer culture. Advertising especially is regarded as a place where rational argument is displaced by pleasure and sex. However, it is hard to find systematic empirical analysis to verify these claims. In this article, I examine the pervasiveness of the ideal of pleasure empirically in television advertising by analysing 167 Finnish advertisements. The findings suggest that the prevailing discourse about hedonistic culture and especially the hedonistic advertising culture captures something essential, but that this discourse does not tell the whole story because it does not notice the flipside, the ideal of the ascetically-oriented body that appears as frequently as the hedonistic ideal.